Influence of Carbon Nano Tubes on the Thermo-Mechanical Properties of Unsaturated Polyester Nanocomposite - A. K. M., Moshiul Alam; Beg, M. D. H.; R. M., Yunus (IOP Publishing, 2015)
To date nano fillers are renowned reinforcing agent for polymer materials. In this work, unsaturated polyester (UPR) nanocomposites were fabricated by 0.1, 0.3 and 0.5 wt% multi walled carbon nanotubes (MWCNTs) through solution dispersion and casting method. The influence of MWCNT content was investigated by thermo-mechanical properties. Dispersion of nanotubes was observed by fracture morphology. The strength of nanocomposites rose with raising the CNT content. Moreover, DSC thermograms of nanocomposites represent noticeable improvement of glass transition temperature (Tg), melting temperature (Tm) and enthalpy (ΔHm). Micro-crystallinity of nanocomposites increased with increasing the CNT content. Moreover, the stiffness increased with increasing the CNT content.